Diagnostic pitfall: Adenoid cystic carcinoma of the tongue presenting as an isolated hypoglossal nerve palsy, case report and literature review. (2016) - Wee, Hide Elfrida; Azhar, Rafay; Tang, Po Yin; Teo, Tze Hern; Iyer, Narayanan Gopalakrishna; Tan, Hiang Khoon; Tan, Ngian Chye
Highlights: Adenoid Cystic Carcinoma is a malignant neoplasm originating in both major and minor salivary glands. It is characterized by slow progression, local invasiveness and perineural invasion. It may present as a hypoglossal nerve palsy. When the diagnosis is in doubt, we suggest examination under anasthesia and deep biopsy. Abstract: Introduction: We describe a patient with an unusual presentation of an isolated hypoglossal nerve palsy as a result of perineural invasion (PI) from adenoid cystic carcinoma (ACC). We will also discuss the diagnostic pitfalls as well as present a short literature review of adenoid cystic carcinomas and suggest improvement to the current diagnostic algorithm for isolated hypoglossal nerve palsies. Presentation of case: A 63 year old Malay female presented with progressive dysphagia and slurred speech for one year. Physical examination showed unilateral right tongue wasting, fasciculation and deviation to the right. An MRI showed atrophy of the tongue due to denervation and subsequently she was treated in a neurology clinic for 8 months. Due to lack of improvement, she was referred to our surgical unit and underwent examination under anaesthesia (EUA) and biopsy. Histology showed adenoid cystic carcinoma with perineural involvement, resulting in lower motor neuron signs. She underwent radiotherapy to the base of her tongue (70 Gy/35#). A PET-CT one month post treatment showed complete response. Discussion: Adenoid cystic carcinoma (ACC) is a salivary gland neoplasm. It is characterized by local invasiveness with frequent recurrence and indolent growth. It affects major salivary glands more than minor salivary glands. In malignancies that have a propensity for PI such as ACC, patients may present atypically with nerve palsies. In infiltrative lesions, the primary tumour may not be evident on magnetic resonance imaging. Therefore, to achieve a diagnosis, a high index of suspicion is required. When the diagnosis is in question, deep biopsy and positron emission tomography may be useful.